Ferromagnetic powder composition and method for producing same
By forming a first coating of compound particles and nanoparticles containing silicate, bismuth and oxygen on the surface of the soft magnetic iron-based core particles, the problem of insufficient performance of soft magnetic core particles in the prior art is solved, higher resistivity and more effective compaction are achieved, and the performance of parts and objects is improved.
Patent Information
- Application Number
- CN202380061105.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-24
- Filing Date
- 2023-08-15
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, the electrical, magnetic and structural properties of soft magnetic core particles have not yet reached the optimal balance, resulting in insufficient performance in a wide range of applications.
The electrical insulation and compaction properties of the core particles are improved by forming a first coating of silicates, bismuth and oxygen of the general formula (K2O)α(SiO2)β on the surface of the soft magnetic iron-based core particles and applying the coating on the surface of the partially covering the core particles.
A higher resistivity and more efficient compaction of the soft magnetic core particles are achieved, thereby improving the density and magnetic properties of parts and objects made from the ferromagnetic powder composition.
Smart Images

Figure CN119768877A_ABST
Abstract
Description
Technical Field
[0001] The technology presented herein generally relates to the field of ferromagnetic powder compositions comprising soft magnetic iron-based core particles and methods of producing ferromagnetic powder compositions.
[0002] background
[0003] Ferromagnetic powders include soft magnetic composite (SMC) powders, which contain soft magnetic core particles, usually iron-based, with an electrically insulating coating on each particle. Such powders can be used to obtain soft magnetic components or parts, such as by compacting the powder into a desired shape. These components or parts (also known as soft magnetic composites) can be used as substitutes for laminated steel components in motors, generators, and electromagnets in a wide range of applications.
[0004] Two key properties of soft magnetic core particles and corresponding components made from such particles are the magnetic permeability μ and the core loss characteristic P. c The magnetic permeability μ of a material indicates its ability to be magnetized or its ability to carry magnetic flux. Maximum magnetic permeability (μ max ) is defined as B / H, the highest value of the ratio of the magnetizing force B or electric field strength to the induced magnetic flux H. When a magnetic material is exposed to a changing electric field, energy losses occur due to both hysteresis losses and eddy current losses. Hysteresis losses (DC losses), which account for the majority of total core losses in most motor applications, are caused by the energy consumption necessary to overcome the magnetic forces trapped in parts made of soft magnetic core particles and are affected by the remanence or residual magnetism B. R and coercivity H C Influence.
[0005] The magnetic forces retained in the assembly can be minimized by improving the quality and purity of the soft magnetic core particles and, in particular, by heat treating the assembly to relieve the stresses caused by the compaction shear forces in the assembly. Energy losses are further caused by eddy current losses (AC losses), which are caused by current induction in the part due to flux changes caused by alternating current (AC) conditions. Eddy current losses are minimized by an electrically isolating coating on each particle, which thereby isolates the soft magnetic core particles from each other. Therefore, the resistivity R of the coating becomes an important parameter for defining the properties and usability of the soft magnetic core particles. The level of resistivity R required to minimize AC losses in a part made of soft magnetic core particles depends on the size distribution of the soft magnetic core particles, the size of the part and the frequency of the alternating magnetic field in which the part is to be used.
[0006] EP 2 252 419 B1 generally discloses a ferromagnetic powder composition comprising soft magnetic iron-based core particles, wherein the surface of the core particles is provided with a first inorganic insulating layer and at least one metal organic layer located outside the first layer.
[0007] US 10,741,316 generally discloses a ferromagnetic powder composition comprising soft magnetic iron-based core particles, wherein the surface of the core particles is coated with at least one phosphorus-based inorganic insulating layer and subsequently at least partially covered with a metal organic compound.
[0008] EP 3 411 169 B1 generally discloses a powder mixture comprising phosphorus-coated iron alloy particles and phosphorus-coated iron particles.
[0009] WO 2020 / 252551 generally relates to a granular material comprising ferromagnetic particles, which are covered by at least one oxide layer consisting of nanoparticles and at least one glass layer covering the oxide layer.
[0010] Despite the advantages brought by the techniques described in the above-mentioned prior art documents, there is still a need to provide ferromagnetic powder compositions comprising soft magnetic core particles having improved electrical, magnetic and structural properties.
[0011] Purpose
[0012] The main objective of the technology presented herein is to provide ferromagnetic powder compositions and mixtures comprising soft magnetic core particles having improved electrical, magnetic and / or structural properties.
[0013] Another object of the technology presented herein is to provide ferromagnetic powder compositions and mixtures comprising soft magnetic core particles that provide an improved balance between two or more of electrical, magnetic and structural properties.
[0014] Another object of the technology proposed herein is to provide a method for producing a powder composition comprising soft magnetic core particles.
[0015] Still another object of the technology proposed herein is to provide a method for manufacturing an object from the ferromagnetic powder composition or mixture.
[0016] Other objects of the technology presented herein include an object made from the ferromagnetic powder composition or mixture and an object comprising the compacted ferromagnetic powder composition or mixture.
[0017] Overview
[0018] At least one of the above objects or at least one of the other objects that will be apparent from the following description is achieved according to the respective first and second aspects of the technology proposed herein by a ferromagnetic powder composition and a method for producing a ferromagnetic powder composition, the ferromagnetic powder composition comprising:
[0019] (i) soft magnetic iron-based core particles,
[0020] (ii) a first coating layer at least partially covering the surface of the core particle and in direct contact with the surface of the core particle,
[0021] One coating contains:
[0022] a. General formula (K2O) α (SiO2) β silicate, wherein α is the molar number of K2O, β is the molar number of SiO2 and the β / α molar ratio is in the range of 0.5-4.1,
[0023] i. wherein the silicate is present in an amount of 0.02-1.0 wt % based on the total weight of the ferromagnetic powder composition,
[0024] b. Particles comprising a compound of bismuth and oxygen having a D in the range of 0.1-10 μm measured according to SS-ISO 13320-1 50 ,and
[0025] cD 50 Nanoparticles of 10-200 nm measured according to SS-ISO 13320-1, and the method comprises the following steps:
[0026] (i) providing a soft magnetic iron-based core particle,
[0027] (ii) contacting the soft magnetic iron-based core particles with a first aqueous solution, the first aqueous solution comprising:
[0028] a. General formula (K2O) α (SiO2) β silicate, wherein α is the molar number of K2O, β is the molar number of SiO2 and the β / α molar ratio is in the range of 0.5-4.1,
[0029] i. wherein the silicate is present in an amount of 0.02-1.0 wt % based on the total weight of the ferromagnetic powder composition,
[0030] b. Particles comprising a compound of bismuth and oxygen having a D in the range of 0.1-10 μm measured according to SS-ISO 13320-1 50 ,and
[0031] cD 50 Nanoparticles of 10-200 nm measured according to SS-ISO 13320-1.
[0032] At least one of the above objects or at least one of the other objects that will be apparent from the following description is achieved according to a third aspect of the technology proposed herein by a method for manufacturing an object from the ferromagnetic powder composition or the ferromagnetic powder mixture, the method comprising the following steps:
[0033] (i) compacting the ferromagnetic powder composition or the ferromagnetic powder mixture in a mold at a compaction pressure in the range of 300-2000 MPa, preferably 400-1200 MPa, to obtain a compacted part, and
[0034] (ii) heat treating the compacted part in a non-reducing atmosphere preferably containing 0-22 wt. %, more preferably 0.5-2 wt. % oxygen (O2) at a temperature in the range of 300-800°C, preferably 400-750°C, more preferably 600-700°C to obtain the object.
[0035] At least one of the above-mentioned purposes or at least one of the other purposes as will become apparent from the following description will be achieved according to the corresponding fourth and fifth aspects of the technology presented herein by an object obtained by a method according to the third aspect of the technology presented herein and an object comprising a compacted ferromagnetic powder composition or a compacted ferromagnetic powder mixture. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figures 1A-1C SEM and EDS mapping images showing soft magnetic iron-based core particles coated with a silicate first coating.
[0038] Figure 2A-2C SEM and EDS mapping images showing soft magnetic iron-based core particles coated with a silicate first coating further comprising 20 mol % Y2O3 nanoparticles.
[0039] Figure 3 A schematic cross-sectional view of a single particle of a ferromagnetic powder composition according to an embodiment of the first aspect of the technology presented herein is shown, showing a soft magnetic iron-based core particle having a first coating of particles comprising a silicate, nanoparticles, and a compound comprising bismuth and oxygen, and a second coating comprising at least one metal organic compound.
[0040] Detailed Description
[0041] The respective first and second aspects of the technology presented herein relate to a ferromagnetic powder composition comprising:
[0042] (i) soft magnetic iron-based core particles,
[0043] (ii) a first coating layer at least partially covering the surface of the core particle and in direct contact with the surface of the core particle,
[0044] One coating contains:
[0045] a. General formula (K2O) α (SiO2) βsilicate, wherein α is the molar number of K2O, β is the molar number of SiO2 and the β / α molar ratio is in the range of 0.5-4.1,
[0046] i. wherein the silicate is present in an amount of 0.02-1.0 wt % based on the total weight of the ferromagnetic powder composition,
[0047] b. Particles comprising a compound of bismuth and oxygen having a D in the range of 0.1-10 μm measured according to SS-ISO 13320-1 50 ,and
[0048] cD 50 Nanoparticles of 10-200 nm as measured according to SS-ISO 13320-1, and
[0049] A method for producing a ferromagnetic powder composition comprises the following steps:
[0050] (i) providing a soft magnetic iron-based core particle,
[0051] (ii) contacting the soft magnetic iron-based core particles with a first aqueous solution, the first aqueous solution comprising:
[0052] a. General formula (K2O) α (SiO2) β silicate, wherein α is the molar number of K2O, β is the molar number of SiO2 and the β / α molar ratio is in the range of 0.5-4.1,
[0053] i. wherein the silicate is present in an amount of 0.02-1.0 wt % based on the total weight of the ferromagnetic powder composition,
[0054] b. Particles comprising a compound of bismuth and oxygen having a D in the range of 0.1-10 μm measured according to SS-ISO 13320-1 50 ,and
[0055] cD 50 Nanoparticles of 10-200 nm measured according to SS-ISO 13320-1.
[0056] Thus, the technology presented herein is based on the inventors' recognition that the magnetic and electrical properties of ferromagnetic powder compositions and parts made from the ferromagnetic powder compositions can be improved by including nanoparticles in a first coating on soft magnetic iron-based core particles. As observed from the examples and accompanying drawings, including nanoparticles in the first coating appears to result in a more uniform distribution of the coating on the surface of the core particles. This improves electrical insulation between the core particles, resulting in higher resistivity of parts made from the ferromagnetic powder composition. Additionally, a more uniformly distributed coating allows for more efficient compaction of the ferromagnetic powder composition, thereby maintaining or improving the density and magnetic properties of parts and objects made from the ferromagnetic powder composition.
[0057] An additional advantage of the technique presented herein is that the first coating can be applied in a single step using an aqueous solution of the silicate, the particles of the compound comprising bismuth and oxygen, and the nanoparticles.
[0058] In the ferromagnetic powder composition, the silicate, the particles of the compound containing bismuth and oxygen and the nanoparticles are all provided in the same first coating. In other words, the particles of the compound containing bismuth and oxygen and the nanoparticles are dispersed in the silicate in the first coating or have reacted so that the first coating is essentially a glass formed by the silicate and the particles of the compound containing bismuth and oxygen, with the nanoparticles dispersed therein. The particles of the compound containing bismuth and oxygen and the nanoparticles can be substantially uniformly dispersed in the first coating.
[0059] The first coating of the ferromagnetic powder composition can be distinguished from a ferromagnetic powder composition having two separate coatings on a soft magnetic iron-based core particle. For example, the first coating can be distinguished from an oxide layer of the nanoparticles and a glass layer covering the oxide layer.
[0060] It was surprisingly found that it is not necessary to have a first oxide layer to create wetting conditions to anchor the glass layer.
[0061] An advantage of the technology presented herein is that the nanoparticles are provided in the same first coating with the silicate and the particles of the compound comprising bismuth and oxygen. As shown in Example 8, the nanoparticles provide a more uniform distribution in an embodiment of the first coating. In addition, the silicate is in the coating (first coating) that is in direct contact with the surface of the core particle, i.e., the silicate contacts the surface of the core particle. An embodiment of the ferromagnetic powder composition has a substantially uniform distribution of the components of the first coating on the surface of the core particle, thereby improving the electrical insulation and more efficient compaction of the ferromagnetic powder composition.
[0062] The ferromagnetic powder composition comprises a plurality of soft magnetic iron-based core particles.
[0063] The soft magnetic iron-based core particles contain or consist of iron or an iron alloy containing at least 90% iron, preferably at least 99% iron, more preferably at least 99.5% iron. The iron alloy may be an alloy iron Fe-Si with up to 7% by weight, preferably up to 3% by weight, silicon, selected from Fe-Al, Fe-Si-Al, Fe-Ni, Fe-Co, Fe-Ni-Co or a combination or mixture of such alloys. The soft magnetic iron-based core particles may contain a mixture of particles, such as a mixture of iron particles and iron alloy particles or a mixture of particles made of two or more iron alloys. Preferably, the soft magnetic iron-based core particles are made of essentially pure iron, i.e. iron with unavoidable impurities. Preferably, at least 80% by weight, more preferably at least 90% by weight of all core particles have a diameter in the range of 20-1000 μm measured according to ISO 4497.
[0064] Within this range, more specific ranges may be more appropriate depending on the intended use of the part, component or object to be produced from the ferromagnetic powder composition. Thus, for high frequency applications, such as sensors, inductors and converters, preferably at least 80% by weight, more preferably at least 90% by weight, such as at least 99% by weight of the core particles are in the range of 20-75 μm (200 mesh corresponds to a D of about 45 μm) measured according to ISO 4497, based on the total weight of the core particles. 50 For low to medium frequency applications, such as motors, generators and converters, preferably at least 80 wt. %, more preferably at least 90 wt. %, such as at least 99 wt. % of the core particles are in the range of 45-150 μm measured according to ISO 4497 (100 mesh corresponds to a D of about 95-100 μm), based on the total weight of the core particles. 50 For low frequency applications, such as electric motors, preferably at least 80 wt. %, more preferably at least 90 wt. %, such as at least 99 wt. % of the core particles are in the range of 75-380 μm measured according to ISO 4497 (40 mesh corresponds to a D of about 180-210 μm), based on the total weight of the core particles. 50 ).
[0065] The soft magnetic iron-based core particles can be spherical or irregularly shaped, preferably irregularly shaped particles. AD (apparent density) can be between 2.8 and 4.0 g / cm 3 , preferably 3.1-3.7 g / cm 3 between.
[0066] The soft magnetic iron-based core particles can be water atomized, gas atomized or sponge iron powder.
[0067] The first coating at least partially covers the surface of the core particles and is in direct contact with the surface of the core particles. Preferably, the first coating covers at least 50% by weight, such as at least 75% by weight, of all surfaces of the core particles in the ferromagnetic powder composition. More preferably, the first coating covers at least 90% by weight, such as at least 95% by weight, of all surfaces of the core particles in the ferromagnetic powder composition.
[0068] Partial coverage means that the first coating may cover at least 50% of the surface area of at least 50% by weight, such as at least 75% by weight, such as at least 90% by weight of the core particle.
[0069] The first coating typically has an average thickness in the range of 20-100 nm. The coating thickness can be estimated from the magnetic permeability, where for a 40 mesh core a maximum relative permeability of about 3000 corresponds to a thickness of zero and a maximum relative permeability of about 700 corresponds to a thickness of about 20 nm.
[0070] General formula (K2O) α (SiO2) β The silicate is potassium silicate or alternatively known as K-silicate, K-waterglass, potassium waterglass or simply silicate herein.
[0071] The β / α molar ratio (i.e., SiO2 / K2O molar ratio) is in the range of 0.5-4.1. Preferably, the β / α molar ratio is in the range of 2.00-3.75. More preferably, the β / α molar ratio is in the range of 2.5-3.5.
[0072] The silicate is present in an amount of 0.02-1.0 wt %, more preferably 0.05-0.5 wt %, based on the total weight of the ferromagnetic powder composition. Preferably, when at least 80 wt % of the core particles based on the total weight of the core particles are 75 μm or larger, the silicate is present in an amount of 0.05-0.2 wt % based on the total weight of the ferromagnetic powder composition, and when at least 80 wt % of the core particles based on the total weight of the core particles are less than 75 μm, the silicate is present in an amount of 0.1-0.5 wt % based on the total weight of the ferromagnetic powder composition. The first coating can be applied using an aqueous solution as shown and it has been found that when the soft magnetic iron-based core particles are contacted with the solution, substantially all of the silicate and other components, such as nanoparticles and particles of compounds comprising bismuth and oxygen, end up in the first coating. Therefore, the content and ratio between the components in the aqueous solution and the soft magnetic iron-based core particles continue to the content and ratio between the components in the first coating and the soft magnetic iron-based core particles.
[0073] The particles comprising a compound of bismuth and oxygen preferably comprise bismuth oxide and hydroxide. Preferably, D measured according to SS-ISO 13320-1 50 In the range of 0.5-2μm.
[0074] Contacting the soft magnetic iron-based core particles with the first aqueous solution can be carried out by mixing, for example, in a mixer. The result of contacting the soft magnetic iron-based core particles with the first aqueous solution is the formation of a first coating on the magnetic iron-based core particles to at least partially cover the magnetic iron-based core particles. In other words, the method according to the second aspect of the technology proposed herein produces soft magnetic iron-based core particles coated with a first coating, i.e., a ferromagnetic powder composition according to the first aspect of the technology proposed herein. The soft magnetic iron-based core particles coated with the first coating and optionally also coated with the second coating as described below can be alternatively referred to as coated core particles or coated soft magnetic iron-based core particles.
[0075] D measured according to SS-ISO 13320-1 50 The median particle size is defined in SS-ISO 13320-1 as the diameter used on a volume basis, ie 50% by volume of the particles are smaller than this diameter and 50% by volume of the particles are larger than this diameter.
[0076] D measured according to SS-ISO 13320-1 50 For example, this can be determined using a Mastersizer 3000 from Malvern Instruments.
[0077] An alternative parameter for determining the size of nanoparticles is the specific surface area (SSA) [m 2 / g], that is, the particle surface area per gram of particles.
[0078] Therefore, D of 10-200 nm measured according to SS-ISO 13320-1 50 Can be used in 6-120m 2 / g range of specific surface area (SSA) equivalent replacement.
[0079] The SSA of the nanoparticles is preferably determined using the BET method, which is a method for determining the specific surface area of a solid by gas adsorption.
[0080] More preferably the SSA of the nanoparticles is preferably determined according to ISO 9277:2010 or preferably ISO 9277:2022.
[0081] Therefore, D of 10-200 nm measured according to SS-ISO 13320-1 50 Can be measured according to ISO 9277:2010 or preferably ISO 9277:2022 as 6-120 m 2 / g specific surface area (SSA) equivalent replacement.
[0082] Preferably, the specific surface area (SSA) of the nanoparticles is 10-50, more preferably 10-30, such as 15-25, preferably 15-20, and most preferably 18 m 2As stated above, these ranges are preferably determined according to ISO 9277:2010 or preferably ISO 9277:2022.
[0083] The specific surface area can be measured using a Micromeritics TriStar 3000 gas adsorption instrument which calculates the BET surface area.
[0084] For comparison purposes, if the particles are assumed to be spherical, the average diameter of the nanoparticles can be calculated from the specific surface area. The formula for calculating the average particle size (nanometers) is 6000 / (BET surface area, m 2 / g)×(density, g / cm 3 ). For Y2O3 (density 5.01g / cm 3 ), 120, 6, 50, 10 and 18m respectively 2 The specific surface areas of 10, 200, 24, 120 and 67 nm respectively result in average diameters.
[0085] The nanoparticles are preferably selected from Y2O3 nanoparticles, ZrO2 nanoparticles, ZnO nanoparticles, MgOH2 nanoparticles, MgO nanoparticles, CaCO3 nanoparticles, Al2O3 nanoparticles, SiO2 nanoparticles and TiO2 nanoparticles, and the nanoparticles preferably contain Y2O3 nanoparticles or consist of them.
[0086] As can be seen in Example 3a, many different nanoparticles are effective in obtaining improved magnetic properties and electrical properties of objects made from the ferromagnetic powder composition. In addition, Example 3a shows that Y2O3 nanoparticles, also known as yttria and yttrium oxide nanoparticles, provide the best magnetic properties and electrical properties currently considered. The nanoparticles can include a mixture of nanoparticles, such as a mixture of two or more of the listed nanoparticles. However, it is currently preferred that only one type of nanoparticles, such as preferably Y2O3 nanoparticles, is present in the first coating.
[0087] The content of nanoparticles in the first coating is preferably 1-30 mol%, preferably 1-20 mol%, based on the molar content of K (potassium) in the first coating. As can be seen in Examples 1a and 3a, these general molar contents of nanoparticles provide good results. In addition, as a reference, when included in a first coating containing 0.1 wt% potassium silicate with a β / α ratio of 3.4 on 5 kg of soft magnetic iron-based core particles, 20 mol% Y2O3 particles corresponds to 0.94 g Y2O3 particles, i.e. 0.0188 wt% based on the weight of the ferromagnetic powder composition.
[0088] Preferably the nanoparticles have a D of 1-100 nm or 50-200 nm, preferably 1-50 nm, more preferably 5-50 nm, such as 30-50 nm or such as 5-20 nm, such as 10 nm, measured according to SS-ISO 13320-1. 50 .
[0089] More preferably, the nanoparticles have a D of 10-100 nm as measured according to SS-ISO 13320-1. 50 Most preferably, the nanoparticles have a D of 20-100 nm as measured according to SS-ISO 13320-1. 50 .
[0090] The former range corresponds to SSA of 12-120m 2 / g, and the latter range corresponds to SSA of 12-60m 2 / g.
[0091] D measured according to SS-ISO 13320-1 50 Preference is given to 10-100 nm, wherein 90% by weight of the particles should have a maximum diameter between 1-500 nm.
[0092] Alternatively, the nanoparticles have a diameter of 1-100 nm or 50-200 nm, preferably 1-50 nm, more preferably 5-50 nm, such as 30-50 nm or such as 5-20 nm, such as 10 nm. In an embodiment, the nanoparticles typically have a diameter of 10 nm. 50 And nanoparticles of this size have been shown to provide the best results.
[0093] When carrying out the method according to the second aspect of the technology presented herein, it may occur that the provided or obtained nanoparticles agglomerate into agglomerates with a diameter exceeding 200 nm and / or that the agglomerated nanoparticles have a diameter exceeding 200 nm. 50 These agglomerates should preferably be completely or partially disintegrated to obtain a product with the desired D 50 Or as above, nanoparticles with a diameter of 1-200 nm or less or increasing their content are preferred, because nanoparticles well distributed in the first coating are preferred. When the nanoparticles used in the method contain a significant amount of agglomerates and when the nanoparticles are not further disintegrated, it is more effective than when using nanoparticles that do not contain or contain only a small amount of agglomerates and have a lower D 50 The mol % of nanoparticles in the first coating layer can preferably be increased compared to nanoparticles of 0.1 or 0.1 mm in diameter.
[0094] Disintegration preferably occurs before or during preparation of the first aqueous solution or during contacting the soft magnetic iron-based core particles with the first aqueous solution. As an example, sonication may be used for disintegration.
[0095] Preferably the first coating comprises:
[0096] - 10-25 mol %, more preferably 15-22 mol %, such as 20 mol % of Y2O3 nanoparticles based on the K content in the first coating, or
[0097] - 1-20 mol %, preferably 1-15 mol %, more preferably 1-10 mol %, such as 5 mol % of ZrO2 nanoparticles based on the K content in the first coating, or
[0098] - Based on the content of K in the first coating, it is 1-20 mol%, preferably 5-20 mol%, more preferably 10-
[0099] 20 mol% MgOH2 nanoparticles, or
[0100] - Based on the content of K in the first coating, it is 1-20 mol%, preferably 5-20 mol%, more preferably 10-
[0101] 20 mol% CaCO3 nanoparticles, or
[0102] - Based on the content of K in the first coating, it is 1-20 mol%, preferably 5-20 mol%, more preferably 10-
[0103] 20 mol% ZnO nanoparticles, or
[0104] - Based on the content of K in the first coating, it is 1-30 mol%, preferably 10-30 mol%, more preferably 15-
[0105] 25 mol%, such as 20 mol% of MgO nanoparticles, or
[0106] - Based on the content of K in the first coating, it is 1-30 mol%, preferably 10-30 mol%, more preferably 15-
[0107] 25 mol%, such as 20 mol% TiO2 nanoparticles, or
[0108] - Al2O3 nanoparticles having a content of 1-20 mol %, preferably 5-15 mol %, more preferably 10 mol %, based on the K content in the first coating, or
[0109] - ZnO nanoparticles in an amount of 1-20 mol %, preferably 1-10 mol %, more preferably 5 mol %, based on the K content in the first coating.
[0110] Examples 1a and 3a show that various nanoparticles at these levels give good results. As above, different nanoparticles according to these ranges can be combined in the first coating.
[0111] Preferably, the content of particles comprising a compound of bismuth and oxygen in the first coating is 0.025-0.3 wt %, preferably 0.05-0.25 wt %, more preferably 0.07-0.22 wt %, such as 0.08-0.22 wt %, such as 0.08-0.11 wt %, based on the total weight of the ferromagnetic powder composition.
[0112] Example 3a shows that particles comprising compounds of bismuth and oxygen in these content ranges give good results.
[0113] The content of 0.08-0.11 wt % is currently the best range for the soft magnetic iron-based core particles having a size of 100 mesh.
[0114] When the soft magnetic iron-based core particles are larger, for example 40 mesh in size, the content of particles containing the bismuth compound is preferably at least 0.05 wt%, such as 0.05-0.10 wt%.
[0115] When the soft magnetic iron-based core particles are smaller, for example, 200 mesh in size, the content of particles containing bismuth compounds is preferably at least 0.15 wt%, such as 0.15-0.30 wt%.
[0116] The compound containing bismuth and oxygen may be selected from bismuth (III) oxide (Bi2O3) and bismuth (III) hydroxide (Bi(OH)3), wherein the compound containing bismuth and oxygen is preferably Bi(OH)3. As shown in Examples 1a and 1b and Example 2, the presence of Bi2O3 or Bi(OH)3 particles increases the resistivity. In addition, as shown in Example 1b, Bi(OH)3 particles increase the resistivity more than Bi2O3 particles.
[0117] Disclosed herein is a ferromagnetic powder composition as described above, wherein the first coating is applied by contacting the soft magnetic iron-based core particles with a first aqueous solution, the first aqueous solution comprising:
[0118] General formula (K2O) α (SiO2) β a silicate, wherein α is the number of moles of K2O, β is the number of moles of SiO2 and the β / α molar ratio is in the range of 0.5-4.1, wherein the silicate is present in an amount of 0.02-1.0 wt % based on the total weight of the ferromagnetic powder composition,
[0119] Particles comprising a compound of bismuth and oxygen having a D50 in the range of 0.1-10 μm measured according to SS-ISO 13320-1, and
[0120] Nanoparticles with a D50 of 10-200 nm as measured according to SS-ISO 13320-1.
[0121] The ferromagnetic powder composition preferably further comprises:
[0122] (iii) a second coating layer at least partially covering the surface of the core particle and / or the first coating layer, the second coating layer comprising:
[0123] a. at least one metal organic compound having the general formula:
[0124] R1[(R1) x (R2) y (M)] n O n-1 R1(I)or
[0125] R2[M(OH) 2(n+1) ] (n+1) O (n) R2 (II)
[0126] wherein M is selected from Si, Ti, Al and Zr; O is oxygen; R1 is a hydrolyzable group; R2 is an organic moiety and wherein at least one R2 contains at least one amino group; wherein n is the number of repeating units and is an integer from 1 to 20; wherein x is 0 or 1; and wherein y is 1 or 2 and x+y is 2,
[0127] The content of the at least one metal organic compound is 0.05-0.40 wt %, preferably 0.1-0.30 wt %, based on the total weight of the ferromagnetic powder composition.
[0128] The second coating further improves the electrical, structural and magnetic properties of components or parts made from the ferromagnetic powder composition.
[0129] R1 can be an alkoxy group with less than 4, preferably less than 3 carbon atoms. R2 is an organic structural part, which means that the R2 group contains an organic part. R2 preferably contains 1-6, more preferably 1-3 carbon atoms. R2 can further include one or more heteroatoms selected from N, O, S and P. The R2 group can be linear, branched, cyclic or aromatic. R2 can include one or more of the following functional groups: amine, diamine, amide, imide, epoxy, hydroxyl, oxirane, urea, urethane, isocyanate, acrylate, glyceryl acrylate, benzylamino, vinylbenzylamino. The R2 group can change between any one of the functional R2 groups and a hydrophobic alkyl group with a repeatable unit.
[0130] When n=1, the metal organic compound is a monomer (formula I) or a dimer (formula II). If the metal organic compound is a monomer, it may be selected from trialkoxy and dialkoxy silanes, titanates, aluminates or zirconates. Therefore, the monomer of the metal organic compound can be selected from 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldiethoxysilane, N-aminoethyl-3-aminopropyl / ethyl / methylalkoxysilane, such as N-aminoethyl-3-aminopropyltrimethoxysilane and N-aminoethyl-3-aminopropylmethyldimethoxysilane, 1,7-bis(triethoxysilyl)-4-azaheptane, triaminofunctional propyltrimethoxysilane, 3-ureidopropyltriethoxysilane, 3-isocyanatepropyltriethoxysilane, tris(3-trimethoxysilylpropyl)isocyanurate, O-(propargyloxy)-N-(triethoxysilylpropyl)urethane, 1-aminomethyltriethoxysilane, 1-aminoethylmethyldimethoxysilane or a mixture thereof.
[0131] When n=2-20, the metal organic compound is an oligomer. The oligomer of the metal organic compound can be selected from alkoxy-terminated alkyl alkoxy oligomers of silanes, titanates, aluminates or zirconates. The oligomer of the metal organic compound can therefore be selected from methoxy-, ethoxy- and / or acetoxy-terminated aminosilsesquioxanes, aminosiloxanes, oligomeric 3-aminopropylmethoxysilanes, 3-aminopropyl / propylalkoxysilanes, N-aminoethyl-3-aminopropylalkoxysilanes or N-aminoethyl-3-aminopropyl / methylalkoxysilanes or mixtures thereof.
[0132] Examples of suitable metal organic compounds include in particular HYDROGEN® from Evonik Industries AG. 1146 and SIVO 203.
[0133] The metal organic compounds also include aqueous amino- or multifunctional silane systems, such as the corresponding silanes supplied by Evonik Industries AG. HYDROSIL products. In these products, the hydrolyzable alkoxy groups are almost completely replaced by hydroxyl groups, i.e. according to formula (II), while the functional groups are similar, for example a hydrophobic alkyl group in combination with an aminoalkyl or diaminoalkyl group. Examples include the HYDROSIL 2627, 2776 and 1151 silane systems. Examples of such compounds may be 1,3-bis(3-aminopropyl)disiloxane-1,1,3,3-tetraol or (3-aminopropyl)({[(propyl)dihydroxysilyl]oxy})silanediol.
[0134] Example 5 shows that various metal organic compounds in the second coating can be successfully used in the ferromagnetic powder composition.
[0135] Preferably, the at least one metal-organic compound has the general formula (I). Alternatively, the at least one metal-organic compound has the general formula (II).
[0136] The ferromagnetic powder composition preferably further comprises a lubricant, preferably a particulate lubricant.
[0137] Including a lubricant in the ferromagnetic powder composition improves compaction and causes the density and strength of the object manufactured by the ferromagnetic powder composition to increase. The lubricant can be selected from primary and secondary fatty acid amides, trans amides (bisamides) or fatty acid amides or alcohols. The lubricating structural part of the lubricant can be a saturated or unsaturated chain containing 12-22 carbon atoms. The lubricant can preferably be selected from stearamide, erucamide, stearyl erucamide, erucyl stearamide, behenyl alcohol, erucyl alcohol, ethylene bis stearamide (i.e. EBS or amide wax). Preferably, the lubricant is an amide wax. Also preferably, a mixture of stearamide or behenyl alcohol and amide wax. An example is 0.1% by weight stearamide combined with 0.3% by weight amide wax.
[0138] The lubricant may be present in an amount of 0.05-0.80 wt %, preferably 0.20-0.40 wt % of the ferromagnetic powder composition. Example 6 shows that a variety of different lubricants can be used.
[0139] The ferromagnetic powder composition according to the first aspect of the technology presented herein is preferably used in a ferromagnetic powder mixture.
[0140] The ferromagnetic powder mixture may contain:
[0141] - a ferromagnetic powder composition according to the first aspect of the technology presented herein, and
[0142] - other ferromagnetic powder compositions,
[0143] The other ferromagnetic powder composition comprises soft magnetic iron-based core particles different from the soft magnetic iron-based core particles of the ferromagnetic powder composition, and preferably the soft magnetic iron-based core particles of the other ferromagnetic powder composition comprise or consist of an iron alloy having a higher resistivity than the soft magnetic iron-based core particles of the ferromagnetic powder composition.
[0144] This is advantageous because it allows further adjustment of the magnetic and electrical properties of the components or parts manufactured from the ferromagnetic powder composition. If, as is preferred, the soft magnetic iron-based core particles of the other ferromagnetic powder composition contain or consist of an iron alloy having a higher resistivity than the soft magnetic iron-based core particles of the ferromagnetic powder composition, the ferromagnetic powder mixture has lower core losses at higher frequencies. In addition, as surprisingly shown in Example 7a, the ferromagnetic powder mixture also has a mechanical strength (TRS) exceeding the acceptable level when the tested weight % (30 weight %) of the other ferromagnetic powder composition is added. This allows the content of the other ferromagnetic powder composition with its iron alloy-based core particles to be increased by more than 30 weight %, and thus provides for the manufacture of usable components, which have even lower total core losses at higher frequencies due to acceptable mechanical strength.
[0145] The soft magnetic iron-based core particles of the further ferromagnetic powder composition preferably comprise or consist of an iron alloy selected from the group consisting of FeSI, FeAl, FeSiAl, FeNi, FeCo and FeNiCo or a combination or mixture of such alloys. Particularly preferred are FeSI (usually 3-6.8 wt. % Si) and FeSiAl (also known as Sendust; usually 9 wt. % Si and 6 wt. % Al).
[0146] The content of the other ferromagnetic powder composition may be up to 60 wt%, such as 30-60 wt%, but typically 10-50 wt%, such as 20-40 wt%, such as 20-30 wt%, based on the weight of the ferromagnetic powder mixture (with the ferromagnetic powder composition according to the first aspect of the technology presented herein constituting the remainder).
[0147] In the powder mixture, the soft magnetic, iron-based core particles of the ferromagnetic powder composition preferably comprise or consist of substantially pure iron, ie iron with unavoidable impurities.
[0148] Preferably, the other ferromagnetic powder composition further comprises a coating or surface treatment on the soft magnetic iron-based core particles therein. The coating or surface treatment preferably comprises a first coating as described above and optionally also a second coating. However, generally when an iron alloy is included, the soft magnetic iron-based core particles of the other ferromagnetic powder composition may be coated or treated with a less insulating coating or treatment, such as by treatment with phosphoric acid in acetone, for example, due to the higher resistivity of the iron alloy compared to substantially pure iron and due to the ability of the coating to withstand heat treatment at higher temperatures, such as 700°C.
[0149] The soft magnetic iron-based core particles of the other ferromagnetic powder composition preferably have the same particle size as the soft magnetic iron-based core particles of the ferromagnetic powder composition according to the first aspect of the technology presented herein as further described above.
[0150] The method according to the second aspect of the technology presented herein may further include one or more of the following steps:
[0151] (iii) drying the coated soft magnetic iron-based core particles, and / or (iv) contacting the coated soft magnetic iron-based core particles with at least one metal organic compound as described above,
[0152] and / or (v) mixing the coated soft magnetic iron-based core particles with a lubricant as described above.
[0153] The step (iii) is preferably performed after the step (ii). The step (iii) may be performed by heating the soft magnetic iron-based core particles while stirring.
[0154] Step (iv) is preferably carried out after step (ii) or (iii) and before step (v).
[0155] Step (v) is preferably performed after step (iii) and step (iv).
[0156] A third aspect of the technology presented herein relates to a method for manufacturing an object from the ferromagnetic powder composition or the ferromagnetic powder mixture, comprising the following steps:
[0157] (i) pressing in a mold at a compaction pressure in the range of 300-2000 MPa, preferably 400-1200 MPa
[0158] compacting the ferromagnetic powder composition or the ferromagnetic powder mixture to obtain a compacted part, and
[0159] (ii) heat treating the compacted part in a non-reducing atmosphere preferably containing 0-22 wt%, more preferably 0.5-2 wt% O2 at a temperature in the range of 300-800°C, preferably 400-750°C, more preferably 600-700°C to obtain the object.
[0160] The compaction can be cold die compaction, warm die compaction or high speed compaction, preferably controlled die temperature compaction (50-120°C) using unheated powder. During compaction, the coated soft magnetic iron-based core particles are pressed together and deformed to adhere to each other and form the compacted part. During the heat treatment, the particles of the compound comprising bismuth and oxygen, together with the nanoparticles and silicates in the first coating and the amino and / or alkyl groups of the metal organic compound of the second coating, form a uniformly distributed bismuth-silicate glass on the surface of the soft magnetic iron-based core particles, which provides the desired resistivity between individual particles of the compacted and heat-treated ferromagnetic powder composition in the finished product. Additionally, the heat treatment reduces the stress formed during compaction.
[0161] The heat treatment process can be carried out in a vacuum, non-reducing, inert or weakly oxidizing atmosphere, for example in 0.01-3 wt % oxygen in nitrogen. In one embodiment, a substantially pure nitrogen atmosphere is used as a non-reducing atmosphere. In one embodiment, 0-22 wt % oxygen, preferably 0.5-2 wt % oxygen, is added. Optionally, the heat treatment is carried out in an inert atmosphere and then quickly exposed to an oxidizing atmosphere, such as a 0.5-22 wt % oxygen / nitrogen mixture or a steam / nitrogen mixture, to build a higher strength and / or corrosion resistant surface shell. In one embodiment, the temperature can be up to 800°C.
[0162] The respective fourth and fifth aspects of the technology presented herein relate to an object obtained by the method according to the third aspect of the technology presented herein and an object comprising a compacted ferromagnetic powder composition or a compacted ferromagnetic powder mixture.
[0163] The object may alternatively be referred to as a part or component and may be selected from soft magnetic components of sensors, inductors, converters, transformers, motors and generators. Example
[0164] In the following examples, various ferromagnetic powder compositions containing soft magnetic iron-based core particles according to the first aspect of the technology proposed herein are produced by coating the soft magnetic iron-based core particles with various first and second coatings according to various embodiments of the method according to the second aspect of the technology proposed herein. The ferromagnetic powder compositions are then used to produce test parts or test objects, which are compacted and heat treated according to various embodiments of the method according to the third aspect of the technology proposed herein. Finally, the relevant properties of the finished test parts, such as resistivity Res and permeability μ-max, are studied.
[0165] More specifically, the test parts used in the examples were produced in the following steps:
[0166] Step 1: The soft magnetic iron-based core particles are mixed with a general formula (K2O) having a concentration (based on dry matter content) of 0.1 wt %. α (SiO2) β An aqueous silicate solution (potassium silicate, Sibelco Nordic AB, β / α molar ratio of 3.37, solid content of 14 wt%) was mixed (10 minutes) to form a first coating on the core particles. The aqueous solution further contained one or more additional compounds of interest or additives as specified for each sample. After the initial mixing, the core particles were dried at 60° C. for 1 hour while stirring and then further dried at 120° C. without stirring.
[0167] Step 2: The mixture from step 1 was mixed with silane (oligomeric diamino-functional silane from Evonik Industries AG 1146, 1.5 g in 1 g H2O, unless otherwise specified) was mixed for 5 minutes to form a second coating, and the resulting mixture was dried at 50°C for 2 hours to produce a finished ferromagnetic powder composition comprising coated soft magnetic iron-based core particles.
[0168] Step 3. A lubricant (0.4 wt. % amide wax unless otherwise specified) was added to the ferromagnetic powder composition to facilitate the production of test parts, and the ferromagnetic powder composition was then formed and compacted (800 MPa, mold temperature of 100° C.) into test parts, which were heat treated to relieve stress from compaction to form finished test parts.
[0169] Unless otherwise specified, the soft magnetic iron-based core particles are water-atomized annealed iron powders with a size of 100 mesh and a particle size of 3.32 g / cm 3 The apparent density of .
[0170] The heat treatment was carried out in three stages in a preheating furnace. The three stages included a delubrication stage at about 300-400°C, during which the compacted parts were heated to a curing stage; a curing stage at about 350-450°C (a first time and temperature given for each sample), in which the coating was cured to result in the formation of an electrically insulating bismuth-silicate glass from the first and second coatings, and a relaxation stage at 600-700°C (a second time and temperature given for each sample), in which stresses from the compaction were released. Unless otherwise specified, the oxygen partial pressure during the heat treatment was 15000 ppm (1.5 wt% oxygen in nitrogen).
[0171] The finished test parts (OD55 / ID45 / H5mm magnetic square ring tube) were tested to determine:
[0172] Resistivity (Res) - How well the material resists the flow of electricity [μΩm]. Measured using a 4-point probe method with a distance of 20mm between the measuring points.
[0173] Coercivity at 10kA / m*(H c )[A / m]
[0174] Maximum Permeability* (μ-max)—The maximum value [unitless] of the ratio between the magnetizations that a material can achieve in response to an applied magnetic field.
[0175] Square ring tube density (d) - the density of the square ring tube test part [g / cm 3 ].
[0176] Magnetic Flux Density*—The induction obtained for a given applied magnetic field [T].
[0177] B4*—magnetic flux density [T] at 4 kA / m,
[0178] B10*—Magnetic flux density at 10kA / m [T]
[0179] Total Core Loss* (at 1T / 1kHz)—The total core loss obtained for the test part at a given inductance and frequency [W / kg].
[0180] *For the measurement of magnetic properties, the square ring tube was wound with 100 drive turns and 100 sense turns of resin coated copper wire (0.63 mm diameter) and measured using a Brockhaus MPG 200D. Reference: IEC 60404-4 (DC measurement) and IEC 60404-6 (AC measurement).
[0181] TRS — Transverse rupture strength [MPa] on a rod with dimensions 30х12х6 mm according to SS-EN ISO 3325:2000.
[0182] AD - Apparent density [g / cm2] measured according to ISO standard 3923-1:2018 as the ratio between the dry mass and the apparent volume of a powder sample 3 ].
[0183] FLOW – Hall flow rate [seconds] according to SS-EN ISO 4490:2018.
[0184] GS—Green strength [MPa] measured on a test part as TRS but before heat treatment.
[0185] Example 1a: Oxygen content in the first coating layer in a heat treated molded component for a given coercivity Hc@10 kA / m Yttrium (Y2O3) nanoparticles improve resistivity R and magnetic permeability μ-max
[0186] Example 1a tested the effect of including 10, 20 and 30 mol % (based on the molar weight of K) of Y2O3 nanoparticles (nominal 10 nm) and 0.1 wt % of bismuth oxide (Bi2O3) in the aqueous silicate solution in step 1 when producing coated soft magnetic iron-based core particles in step 2. This test resulted in four different test parts prepared according to step 3, which were tested to determine their properties relative to reference 1 and reference 2 as listed in Table 1a below.
[0187] Reference 2 is included to provide additional reference data for the nanoparticle samples. Reference 2 was produced using an alternative method using phosphoric acid. Specifically, step 1 is divided into sub-steps 1a-1c in this alternative method, wherein:
[0188] - Sub-step 1a comprises mixing the soft magnetic iron-based core particles with the general formula (K2O) α (SiO2) βand drying the mixture to obtain dry particles,
[0189] - Sub-step b consists of treating the dried granules with dilute phosphoric acid (25-75 g / l water), and
[0190] - Sub-step c consists of mixing the particles with bismuth oxide (Bi2O3).
[0191] Table 1a
[0192]
[0193]
[0194] As can be seen from the results, including 20mol% Y2O3 nanoparticles (sample 1-2) provides a resistivity of 3368μΩm and a coercivity of 134.8A / m under a heat treatment of 450 / 650°C. In contrast, the reference 1 sample provides a significantly lower resistivity of 1435μΩm. Sample 1-2 also provides a higher μ-max and a lower total core loss. Therefore, sample 1-2 provides overall better performance than the reference 1 sample for forming a soft magnetic component or part.
[0195] Furthermore, it can be seen that in order to reach a coercivity of 135.2 similarly low as Reference Sample 1 and Sample 1-2, the Reference 2 sample must be heat treated at a higher temperature of 450 / 670° C. However, this results in an even lower resistivity of 1053 μΩm.
[0196] Table 1a further shows that including 20 mol% Y2O3 nanoparticles (sample 1-2) provides overall better performance than 10 mol% (sample 1-1) and 30 mol% (sample 1-3) (these samples have lower resistivity). However, sample 1-1 provides moderate resistivity, lowest coercivity and highest permeability under heat treatment at 450 / 650°C.
[0197] Additionally, Table 1a also shows that under both heat treatments, bismuth hydroxide (Bi(OH)3 significantly increases the resistivity (sample 4) compared to bismuth oxide (Bi2O3) (samples 1-2), however the magnetic permeability is slightly lower. Without wishing to be bound by theory, it is believed that this is due to the fact that the hydroxide is not easily reduced by the carbon in the metal organic compound second layer.
[0198] Therefore, from Example 1a, it can be concluded that the amount of Y2O3 nanoparticles in the first coating can be appropriately 10-30 mol%, preferably 15-25 mol%, more preferably 18-22 mol%, such as 20 mol%, based on the amount of K in the silicate. It can be further concluded that including Y2O3 nanoparticles provides better performance than using phosphoric acid to treat the core particles according to this alternative method. It can be further concluded that the first coating can contain bismuth oxide (Bi2O3) or bismuth hydroxide (Bi(OH)3), preferably bismuth hydroxide (Bi(OH)3).
[0199] Unless otherwise specified in other examples below, bismuth hydroxide (Bi(OH)3) was used at a concentration of 0.08 wt%. In addition, unless otherwise specified, the nanoparticles were nominally D 50 Y2O3 nanoparticles having a diameter of 10 nm and a nanoparticle content of 20 mol % based on the amount of K in the silicate first coating.
[0200] Example 1b: Additional Experiments Using 20 mol % Y2O3 Nanoparticles - Effect of Silicate Concentration and Silane Concentration
[0201] Other tests were carried out using the same conditions as in Example 1a, but with different contents of the first and second coatings, i.e. different silicate and silane concentrations (under heat treatment at 450 / 650°C (30 / 30 min)). The test parameters and results are shown in Table 1b below:
[0202] Table 1b
[0203]
[0204] As can be seen from the table, bismuth hydroxide (Bi(OH)3) significantly improves the resistivity (Sample 1-6) compared to bismuth oxide (Bi2O3) (Sample 1-5). Reducing the silane content in the second coating by half still produces acceptable resistivity (Sample 1-7). Reducing the addition of the first coating (silicate, Bi(OH)3 and Y2O3) by half produces low resistivity (Sample 1-8, Sample 1-9).
[0205] From Example 1b it can be concluded that the silane content in the second coating can be reduced compared to Example 1a while maintaining acceptable resistivity values.
[0206] Example 2: Other experiments using different core particle sizes
[0207] Further tests were conducted to determine that the addition of nanoparticles to an aqueous silicate solution, ie a first coating, provides benefits for a wide range of core particle sizes (mesh) and apparent densities (AD). The test parameters and results are shown in Table 2 below (heat treatment at 450 / 650°C (30 / 30 min)).
[0208] Table 2
[0209]
[0210] Thus, the results show that soft magnetic iron-based core particles having different sizes can be effectively coated with the first and second coating layers.
[0211] Additionally, the results show that the first and second coatings provide good resistivity to soft magnetic iron-based core particles having different apparent densities. The apparent density has a significant influence on the mechanical strength and coercivity and thus the overall core losses.
[0212] Additionally, the results show that good results can be obtained for different silicate concentrations in the first coating and different silane concentrations in the second coating.These amounts can be further adjusted to optimize both resistivity and permeability.
[0213] Example 3a: Further experiments using different types of nanoparticles
[0214] Other tests were conducted to determine whether the Y2O3 nanoparticles could be replaced by other nanoparticles while providing the same or similar improvements in the performance of the test parts. The test parameters and results are shown in Table 3a below (heat treatment at 450 / 650°C (30 / 30min)). Three series of tests were carried out corresponding to three reference samples (ref1, ref2, ref3). Due to the inevitable variations between the test series, the properties measured for each sample are only fully comparable to those of other samples with the same reference, i.e. belonging to the same test series. Comparison between samples from different test series is still possible. Unless specified, the AD of the soft magnetic iron-based core particles used is 3.35 g / cm 3 .
[0215] Table 3a
[0216]
[0217]
[0218] As can be seen from the table, nanoparticles of ZrO2, Mg(OH)2, CaCO3, ZnO, MgO, TiO2, and Al2O3 can also be used in the first coating to improve resistivity. However, among these materials, Y2O3 nanoparticles provided the best overall performance for the tested parts.
[0219] ZrO2 and ZnO nanoparticles show enhanced resistivity for lower molar concentrations (maximum 2.5 mol% and 5 mol%, respectively).
[0220] Example 3b: Additional experiments using different nanoparticle diameters
[0221] Additional experiments were conducted to explore the effect of Y2O3 nanoparticles of various diameters. The β / α molar ratio was 3.2. The experimental parameters and results are shown in Table 3b below (heat treatment at 450 / 650°C (30 / 30 min)).
[0222] Table 3b
[0223]
[0224] As can be seen from the table, nanoparticles of various sizes perform well in the first coating and provide good electrical and magnetic properties. In addition, the yttrium oxide product nominally designated as 0.5 to 1.0 μm contains an average particle size D 50 Agglomerates of nanoparticles with a size of 200 nm.
[0225] Example 4 - Additional Experiments Using Different β / α Molar Ratios and Silicate Concentrations
[0226] Additional tests were conducted to explore the effects of various β / α molar ratios (SiO2 / K2O) and different silicate concentrations in the first coating. The test parameters and results are shown in Table 4 below (heat treatment at 450 / 650°C (30 / 30 min)). 0.08 wt% Bi(OH)3 was used in each sample.
[0227] Table 4
[0228]
[0229]
[0230] As can be seen from the table, a β / α ratio of 2.5 gives slightly better resistivity results. The table further shows that if the weight % of silicate is increased (e.g. doubled to 0.2 weight %), the mol % of Y2O3 nanoparticles can be reduced (e.g. halved to 10 mol %). Note that for the two selected β / α ratios, the total amount of nanoparticles added is the same, i.e. the molar content of nanoparticles to silicon remains constant.
[0231] Example 5: Additional Tests Using Different Metal-Organic Compounds for Second Coating
[0232] Other tests were conducted to determine the effects of various Metal organic compounds Replacement Standard Effect of 1146 Silane. The test parameters and results are shown in Table 5 below (Heat treatment at 450 / 650°C (30 / 30 min)).
[0233] Table 5
[0234]
[0235] As can be seen from Table 5, all the metal organic compounds containing at least one amino group, ie, all samples except 7-154, provide good resistivity values and TRS values.
[0236] Example 6—Other Tests Using Different Lubricants
[0237] Additional tests were conducted to determine the effects of various lubricants on the properties of the test parts. The test parameters and results are shown in Table 6 below.
[0238] Table 6
[0239]
[0240]
[0241] As can be seen from the table, the choice of lubricant has only a limited effect on the electrical and magnetic properties. Therefore, different lubricants can be used.
[0242] Example 7a: Other methods using a mixture of a ferromagnetic powder composition and other or additional ferromagnetic powder compositions He tested
[0243] Other tests were conducted to determine whether the ferromagnetic powder composition could be mixed with other ferromagnetic powder compositions containing soft magnetic core particles, especially alloy core particles. The alloy core particles can provide lower core losses for manufactured parts for high frequency applications due to their greater internal resistivity, and therefore these tests explored the feasibility of such mixtures and their effect on the performance of the manufactured parts. The test parameters and results are shown in Table 7a below.
[0244] Table 7a
[0245]
[0246] As can be seen from the table, the incorporation of alloy core particles provides increased resistivity and reduced total core losses. At the same time the mechanical strength (TRS) is reduced, however, the TRS is maintained at more than acceptable levels, which is believed to be caused by the increased TRS of the ferromagnetic powder composition compared to prior art ferromagnetic powder compositions with other types of coatings. This means that the content of the other ferromagnetic powder composition, i.e. the content of alloy core particles, can be increased to more than 30% by weight tested, such as up to 50% by weight or even up to 60% by weight, and thus provide a component that can be used for manufacturing, which has even lower total core losses at higher frequencies due to acceptable mechanical strength.
[0247] These advantages are especially useful for passive components (transformers, inductors) manufactured from 200-300 mesh core particles.
[0248] Example 7b: Effect of Thermal Aging
[0249] Additional tests were performed to determine the effect of heat aging on the properties of the test parts. The test parameters and results are shown in Table 7b below:
[0250] Table 7b
[0251]
[0252] As shown in the table, the core loss variation, i.e. the increase in core loss, of the test part is smaller compared to the reference part. Thus, the ferromagnetic powder composition according to the first aspect of the technology presented herein provides for the manufacture of components with improved thermal stability due to good distribution and high surface coverage of the first coating on the core particles. This is advantageous in applications subjected to high temperatures, i.e. at 200°C or higher, such as at 200-260°C.
[0253] Example 8: Surface inspection using SEM / EDS
[0254] For this example, similar to step 1 described above, the soft magnetic iron-based core particles were mixed with a general formula (K2O) having a β / α ratio of 3.1-3.4 and a concentration of 0.1 wt % α (SiO2) β Aqueous solutions of silicates were mixed with or without 20 mol % Y2O3 nanoparticles (10 nm).
[0255] The core particles were examined using a field emission gun scanning electron microscope (FEG-SEM) (Hitachi SU6600) with an energy dispersive spectroscopy detector (Oxford Instruments Ultima Max 65 mm). The measurements were performed at a distance of 10 mm (working distance) using an accelerating voltage of 20 kV. The results are shown in Figures 1A-1C and Figure 2A-2C As shown and further summarized in Table 8 below. Figure 1A SEM image showing a core particle coated with silicate but without nanoparticles. Figure 2A SEM images of core particles coated with silicate and nanoparticles are shown. Comparison of these images shows that Figure 1A Compared with the core particles in Figure 2A The core particles in the Figure 2A The first coating is thinner on the core particle. Figure 1B and 2B The EDS mapping image of the corresponding core particles is shown, which shows the K content on the surface in light grey to white. It can be further observed that the thickness of the first silicate coating varies on the surface, forming thicker parts with high K content called patches, see Figure 1B and 2B, and thinner parts between the sheets. Figure 2B It can be seen that Figure 1B There are many spatially separated K deposits on the core particles coated with silicates and nanoparticles, compared with only a few larger deposits in the MgCl2O3 matrix. Figure 1C and 2C The EDS mapping images of the corresponding core particles are shown, which show the content of Si on the surface in light grey to white. Figure 2C Display and Figure 1C The Si content is more evenly distributed on the surface of the core particles coated with silicate and nanoparticles with many small deposits, compared to the few larger deposits in the core particles.
[0256] Table 8. EDS point element analysis
[0257]
[0258] As shown in the table, the addition of nanoparticles increases the level of Fe detected in the flakes. Since SEM / EDS measurements measure not only the amount of material on the surface of the particles, but also to some extent into the surface (the minimum detection area at 20 kV for EDS point analysis is about 1.5 μm deep and about 1 μm in diameter), the increase in Fe content detected on the flakes for the coating containing nanoparticles (79.8 wt%, bold) indicates that the flakes are thinner and the silicate coating is more evenly distributed on the surface of the core particles. This is supported by the increase in silicon content measured between the flakes for the coating containing nanoparticles (1.10 wt%, bold) compared to the sample without nanoparticles (0.48 wt% Si). Furthermore, the Fe content between the flakes is slightly reduced (93.0 wt% vs. 95.5 wt%), which further indicates a thicker silicate coating. Therefore, by including nanoparticles in the first coating, the silicate becomes more evenly distributed on the surface of the core particles, which correlates with the increase in resistivity observed in the previous examples. The increased number of smaller platelets on the core particles coated with the silicate coating containing nanoparticles further improves the particle behavior during pressing and heat treatment of the particles to form parts or components. This is because the distributed platelets with a relatively high content of potassium have lubricating properties and can therefore protect the first coating during pressing.
[0259] Example 9: Schematic cross-sectional representation of particles of a ferromagnetic powder composition
[0260] Based on the above embodiments, Figure 3A highly schematic cross-sectional illustration of a single particle 10 of a ferromagnetic powder composition according to an embodiment of the first aspect of the technology presented herein is shown. The particle 10 comprises a soft magnetic iron-based core particle 11 covered by a first coating 12 comprising a silicate. A second coating 13 is also shown and comprises a metal organic compound. Particles comprising a compound of bismuth and oxygen and having an approximate diameter of about 1 μm (one of which is marked with reference numeral 14) are shown dispersed within the first coating 12. Additionally, nanoparticles having an approximate diameter of about 200 nm or less (one of which is marked with reference numeral 15) are also shown dispersed within the first coating 12.
[0261] Figure 3 Particles are shown before heat treatment, i.e. before the ferromagnetic powder is compacted and heat treated to produce an object according to the method according to the third aspect of the technology presented herein. During the heat treatment, it is believed that the particles 14 comprising the compound of bismuth and oxygen, together with the nanoparticles 15 and silicate in the first coating 12 and the amino and / or alkyl groups of the metal organic compound of the second coating 13, form a uniformly distributed bismuth-silicate glass, which provides electrical resistivity between the individual particles of the compacted and heat treated ferromagnetic powder composition.
[0262] although Figure 3 Particles 14 of a compound comprising bismuth and oxygen are shown to be present in first coating 12 , but it is contemplated that particles 14 of a compound comprising bismuth and oxygen may additionally be dispersed within second coating 13 .
[0263] In addition, despite Figure 3 The first coating layer 12 and the second coating layer 13 are shown completely covering the soft magnetic iron-based core particles 11 , but one or both of these coating layers may alternatively only partially cover the soft magnetic iron-based core particles 11 .
[0264] Possible modifications of the technique presented in this article
[0265] The technology presented herein is not limited to the embodiments described above and shown in the drawings, which are primarily for illustrative and exemplary purposes. This patent application is intended to cover all adjustments and variations of the preferred embodiments described herein; therefore, the invention is defined by the wording of the appended claims and their equivalents. Therefore, the device can be modified in all kinds of ways within the scope of the appended claims.
[0266] Throughout this specification and the claims that follow, unless the context requires otherwise, the word "comprises" and variations such as "comprises" or "comprising", will be understood to imply the inclusion of a stated integer or step or group of integers or steps but not the exclusion of any other integer or step or group of integers or steps.
Claims
1. A ferromagnetic powder composition comprising: (i) soft magnetic iron-based core particles, (ii) a first coating layer at least partially covering the surface of the core particle and in direct contact with the surface of the core particle, the first coating layer comprising: a. General formula (K2O) α (SiO2) β silicate, wherein α is the molar number of K2O, β is the molar number of SiO2 and the β / α molar ratio is in the range of 0.5-4.1, i. wherein the silicate is present in an amount of 0.02-1.0 wt % based on the total weight of the ferromagnetic powder composition, b. Particles comprising a compound of bismuth and oxygen having a D in the range of 0.1-10 μm measured according to SS-ISO 13320-1 50 ,and cD 50 Nanoparticles of 10-200 nm measured according to SS-ISO 13320-1.
2. The ferromagnetic powder composition according to claim 1, wherein the nanoparticles are selected from the group consisting of Y2O3 nanoparticles, ZrO2 nanoparticles, ZnO nanoparticles, MgOH2 nanoparticles, MgO nanoparticles, CaCO3 nanoparticles, Al2O3 nanoparticles, SiO2 nanoparticles and TiO2 nanoparticles, and wherein the nanoparticles preferably comprise or consist of Y2O3 nanoparticles.
3. A ferromagnetic powder composition according to any preceding claim, wherein the content of the nanoparticles in the first coating is 1-30 mol%, preferably 1-20 mol%, based on the molar content of potassium K in the first coating.
4. A ferromagnetic powder composition according to any preceding claim, wherein the nanoparticles have a D of 10-100 nm measured according to SS-ISO 13320-1. 50 .
5. A ferromagnetic powder composition according to any preceding claim, wherein the first coating comprises: - 10-25 mol %, more preferably 15-22 mol %, such as 20 mol % of Y2O3 nanoparticles based on the K content in the first coating, or - 1-20 mol %, preferably 1-15 mol %, more preferably 1-10 mol %, such as 5 mol % of ZrO2 nanoparticles based on the K content in the first coating, or - MgOH2 nanoparticles having a content of 1-20 mol %, preferably 5-20 mol %, more preferably 10-20 mol %, based on the content of K in the first coating, or - CaCO3 nanoparticles having a content of 1-20 mol %, preferably 5-20 mol %, more preferably 10-20 mol %, based on the content of K in the first coating, or - ZnO nanoparticles containing 1-20 mol %, preferably 5-20 mol %, more preferably 10-20 mol %, based on the K content in the first coating, or - MgO nanoparticles containing 1-30 mol %, preferably 10-30 mol %, more preferably 15-25 mol %, such as 20 mol %, based on the K content in the first coating, or - TiO2 nanoparticles containing 1-30 mol%, preferably 10-30 mol%, more preferably 15-25 mol%, such as 20 mol%, based on the K content in the first coating, or - Al2O3 nanoparticles having a content of 1-20 mol %, preferably 5-15 mol %, more preferably 10 mol %, based on the K content in the first coating, or - ZnO nanoparticles in an amount of 1-20 mol %, preferably 1-10 mol %, more preferably 5 mol %, based on the K content in the first coating.
6. A ferromagnetic powder composition according to any preceding claim, wherein the particles of the compound comprising bismuth and oxygen are present in the first coating in an amount of 0.025-0.3 wt.-%, preferably 0.05-0.25 wt.-%, more preferably 0.07-0.22 wt.-%, such as 0.08-0.22 wt.-%, such as 0.08-0.11 wt.-%, based on the total weight of the ferromagnetic powder composition.
7. A ferromagnetic powder composition according to any preceding claim, wherein the compound comprising bismuth and oxygen is selected from bismuth (III) oxide (Bi2O3) and bismuth (III) hydroxide (Bi(OH)3), wherein the compound comprising bismuth and oxygen is preferably Bi(OH)3.
8. A ferromagnetic powder composition according to any preceding claim, further comprising: (iii) a second coating layer at least partially covering the surface of the core particle and / or the first coating layer, the second coating layer comprising: a. at least one metal organic compound having the general formula: R1 [(R1) x (R2) y (M)] n O n-1 R1(I) or R2[M(OH) 2(n+1) ] (n+1) O (n) R2(II) wherein M is selected from Si, Ti, Al and Zr; O is oxygen; R1 is a hydrolyzable group; R2 is an organic moiety and wherein at least one R2 contains at least one amino group; wherein n is the number of repeating units and is an integer from 1 to 20; wherein x is 0 or 1; and wherein y is 1 or 2 and x+y is 2, The content of the at least one metal organic compound is 0.05-0.40 wt %, preferably 0.10-0.30 wt %, based on the total weight of the ferromagnetic powder composition.
9. A ferromagnetic powder composition according to any preceding claim, further comprising a lubricant, preferably a particulate lubricant.
10. A ferromagnetic powder mixture comprising: - a ferromagnetic powder composition according to any preceding claim, and - other ferromagnetic powder compositions, wherein the other ferromagnetic powder composition comprises soft magnetic iron-based core particles different from the soft magnetic iron-based core particles of the ferromagnetic powder composition, and It is preferred that the soft magnetic iron-based core particles of the other ferromagnetic powder composition include or consist of an iron alloy having a higher resistivity than the soft magnetic iron-based core particles of the ferromagnetic powder composition.
11. A method for producing a ferromagnetic powder composition, comprising the steps of: (i) providing a soft magnetic iron-based core particle, (ii) contacting the soft magnetic iron-based core particles with a first aqueous solution, the first aqueous solution comprising: a. General formula (K2O) α (SiO2) β silicate, wherein α is the molar number of K2O, β is the molar number of SiO2 and the β / α molar ratio is in the range of 0.5-4.1, i. wherein the silicate is present in an amount of 0.02-1.0 wt % based on the total weight of the ferromagnetic powder composition, b. Particles comprising a compound of bismuth and oxygen having a D in the range of 0.1-10 μm measured according to SS-ISO 13320-1 50 ,and cD 50 Nanoparticles of 10-200 nm measured according to SS-ISO 13320-1.
12. The method according to claim 11, further comprising one or more of the following steps: (iii) drying the soft magnetic iron-based core particles, and / or (iv) contacting the soft magnetic iron-based core particles with at least one metal organic compound having the general formula: R1 [(R1) x (R2) y (M)] n O n-1 R1(I) or R2[M(OH) 2(n+1) ] (n+1) O (n) R2(II) wherein M is selected from Si, Ti, Al and Zr; O is oxygen; R1 is a hydrolyzable group; R2 is an organic moiety and wherein at least one R2 contains at least one amino group; wherein n is the number of repeating units and is an integer from 1 to 20; wherein x is 0 or 1; and wherein y is 1 or 2 and x+y is 2, The at least one metal organic compound is present in an amount of 0.05-0.40 wt %, preferably 0.10-0.30 wt %, based on the total weight of the ferromagnetic powder composition, and / or (v) the soft magnetic iron-based core particles are mixed with a lubricant.
13. A method for producing an object from a ferromagnetic powder composition according to any one of claims 1 to 9 or a ferromagnetic powder mixture according to claim 10, comprising the following steps: (i) compacting the ferromagnetic powder composition according to any one of claims 1 to 9 or the ferromagnetic powder mixture according to claim 10 in a mold at a compaction pressure in the range of 300 to 2000 MPa, preferably 400 to 1200 MPa, to obtain a compacted part, and (ii) heat treating said compacted part in a non-reducing atmosphere preferably containing 0-22 wt. %, more preferably 0.5-2 wt. % oxygen (O2) at a temperature in the range of 300-800°C, preferably 400-750°C, more preferably 600-700°C to obtain said object.
14. An object obtainable by a method according to claim 13.
15. An object comprising a compacted ferromagnetic powder composition according to any one of claims 1 to 9 or a ferromagnetic powder mixture according to claim 10.
Citation Information
Patent Citations
Iron-based powder composition
EP3411169B1
Ferromagnetic powder composition and method for its production
US10741316B2
Particulate material for obtaining a soft magnetic composite and particulate material production process for obtaining a soft magnetic composite
WO2020252551A1